Mixed-mode fracture behaviors of AISI 1045 and AISI 5140 steels in compressor crankshafts – Part II: Mode II-III. (March 2020) - Nie, Defu; Chen, Xuedong; Wu, Qiaoguo
Highlights: A modified loading device was used to further investigate the mixed-mode II-III fracture. Load-displacement curves began to deviate from the linear relationships at lower load levels. Fiber and sliding features are shown under mode II loading, but shear feature under other loading. A criterion for mixed-mode II-III fracture was proposed and agreed well with experimental data. Abstract: This is Part II of mixed-mode fracture behaviors of AISI 1045 and AISI 5140 steels used for compressor crankshafts, to further investigate mixed-mode II-III fracture by using a modified loading device based on the mode I-III one. It was found that load-displacement curves began to deviate from linear relationships at lower load levels with increasing loading angle; at the same loading angle, stress-intensity-factor versus displacement curves were similar for specimens with different pre-crack lengths; fracture surfaces mainly showed shear feature (elongated dimples and frictional markings) except the fiber and sliding features under the mode II loading condition; crack propagated in the direction perpendicular to the maximum tangential stress under the mode II loading condition while cracks propagated in the pre-crack planes under other loading conditions. Finally, a criterion for mixed-mode II-III fracture was proposed and its validity for AISI 1045 and AISI 5140 steels has been verified.